Unraveling the Role of Heme in Neurodegeneration - Chiabrando, Deborah; Fiorito, Veronica; Petrillo, Sara; Tolosano, Emanuela (Frontiers in Neuroscience, 2018)
Heme (iron-protoporphyrin IX) is an essential co-factor involved in several biological processes, including neuronal survival and differentiation. Conversely, an excess of free-heme promotes oxidative stress and lipid peroxidation thus leading to cell death. The toxic properties of heme in the brain have been extensively studied during intracerebral or subarachnoid haemorrhages. Recently, a growing number of neurodegenerative disorders have been associated to alterations of heme metabolism. Hence, the etiology of such diseases remains undefined. The aim of this review is to highlight the neuropathological role of heme and to discuss the major heme-regulated pathways that might be crucial for the survival of neuronal cells. The understanding of the molecular mechanisms linking heme to neurodegeneration will be important for therapeutic purposes.